Mechanisms influencing the high prevalence of COVID-19 in diabetics: A systematic review - Jain, Roshni; Mathew, Dennis (Medical Research Archives, 2023)
Diabetics have an increased risk of contracting COVID-19 infection and tend to have more severe symptoms. This systematic review explores the potential mechanisms influencing the high prevalence of COVID-19 infections in individuals with diabetes. It reviews the emerging evidence about the interactions between viral and diabetic pathways, particularly how diabetes physiology could contribute to higher viral reception, viral entry and pathogenicity, and the severity of disease symptoms. Finally, it examines the challenges we face in studying these mechanisms and offers new strategies that might assist our fight against current and future pandemics.